2008
DOI: 10.1002/qua.21906
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of alkali metal atomic clusters: From Lin to Csn (n = 2–8)

Abstract: ABSTRACT:A theoretical study of the electronic structure of the first members of the alkali metal atomic clusters series Li n to Cs n (n ϭ 2-8) has been done. The geometries of some isomers of the neutral, positive, and negative charged clusters have been determined. Some important properties have also been calculated: atomic binding energies, vertical and adiabatic ionization potentials, vertical and adiabatic electron affinities, static dipole polarizabilities, and energy gaps. Whenever possible they have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
5
19
1
Order By: Relevance
“…44 has reported the structure with D 2h symmetry while we have obtained the one with higher symmetry of D 4h , which is consistent with Ref. 47.…”
Section: B Lithium Clusterssupporting
confidence: 92%
“…44 has reported the structure with D 2h symmetry while we have obtained the one with higher symmetry of D 4h , which is consistent with Ref. 47.…”
Section: B Lithium Clusterssupporting
confidence: 92%
“…The chlorine atom is at the apex position in this structure, and the average bond length of Li−Cl is 2.311Å. The lowest energy structure of the Li 7 cluster was found to be a pentagonal bipyramidal [4,5]. The isomer (Fig.…”
Section: Geometrical Structuresmentioning
confidence: 84%
“…1.5a), and the average bond length of Li−Cl is 2.185Å. It was reported that the stable structure of the Li 5 is a pentagon [3,4], and also trigonal bipyramid structure was reported at ground state [5]. Hence, doping of the chlorine atom changes the geometry to the capped planar rhombus.…”
Section: Geometrical Structuresmentioning
confidence: 97%
See 2 more Smart Citations